AI 2010: Advances in Artificial Intelligence 23rd Australasian Joint Conference, Adelaide, Australia, December 7-10, 2010. Proceedings - Li, Jiuyong (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 23rd Australasian Joint Conference on Artificial Intelligence, AI 2010, held in Adelaide, Australia, in December 2010. The 52 revised full papers presented were carefully reviewed and selected from 112 submissions. The papers are organized in topical sections on knowledge representation and reasoning; data mining and knowledge discovery; machine learning; statistical learning; evolutionary computation; particle swarm optimization; intelligent agent; search and planning; natural language processing; and AI applications.